Television food advertising towards children : a content analysis of the Singapore advertising landscape and experimental study on the placement of pro-nutritional advertisements - Lim, Glenn Yin De. (2011)
Food advertising has been recognized as one of the contributing factors to rising childhood obesity. This study aims to examine food and beverage (F&B) advertising as well as persuasion strategies in health communication in the form of pro-nutritional advertisements, in the context of children’s television viewing. In Study One, we mapped out the food advertising landscape by content analyzing F&B advertisements (ads) across six television channels over two weeks in Singapore. Results show that there is a disproportionately large quantity of junk F&B ads and no pro-nutritional advertisement (PNA) by health authorities on Singapore television. In Study Two, an experiment was conducted on 364 children aged 10-13 years old to investigate the effects of message order and time delay on a combination of PNA and F&B ads in influencing children’s food consumption intention. Two-way ANOVA tests reveal that the optimal placement of PNA is when the PNA is placed after F&B ads in the presence of time delay. Children exposed to this condition chose significantly lower amount of total food items and unhealthy food items as compared to other conditions. Results indicated that message order and time delay are pertinent factors in determining the effectiveness of the PNA in moderating the negative effects of F&B ads. Implications on advertising regulations and health promotion are discussed.